Density and Viscosity of Partially Carbonated Aqueous Tertiary Alkanolamine Solutions at Temperatures between (298.15 and 353.15) K - Zhang,J; Fennell,PS; Trusler,JPM (Journal of Chemical and Engineering Data, 2015)
The density and viscosity of partially carbonatedaqueous solutions of either 2-dimethylaminoethanol or 2-diethylaminoethanolwere measured over a temperature range of (298.15 to353.15) K with alkanolamine mass fractions of 0.15 to 0.45.Correlations were developed to represent the density and viscosityof these solutions as a function of amine concentration, CO2 loading,and temperature. For the density, the correlation represents theexperimental data to within ± 0.2 %, while the viscosity data werecorrelated to within ± 4 %. The data and models reported in thispaper will help facilitate a better understanding of the performance ofthese amines in CO2 capture processes, especially in relation to masstransfer and hydrodynamic calculations.